Mindfulness and Self-Compassion as Key Factors in Developing Students’ Emotional Intelligence - Irma Rahmawati; Gian Sugiana Sugara; Anandha Putri Rahimsyah (Edupotensia Foundation, 2025)
Aggressive behavior in the school environment has a significant impact on the learning atmosphere, creating an unsafe environment that disrupts academic processes, affects students' mental health, and influences social relationships at school. This behavior is associated with low levels of emotional intelligence. This study aims to examine the influence of mindfulness and self-compassion on emotional intelligence among students at SMA Negeri 6 Tasikmalaya. The study used multiple correlation analysis, involving 300 students, with data collected through questionnaires measuring levels of emotional intelligence, mindfulness, and self-compassion. Based on the Structural Equation Model (SEM), the structural model for mindfulness and self-compassion on emotional intelligence demonstrated positive and significant results. A positive correlation was found between mindfulness and emotional intelligence (r=0.230; p=<0.001). Self-compassion showed a positive correlation with emotional intelligence (r=0.647; p=<0.001). Together, these two variables contributed 46.1% to emotional intelligence. These findings indicate that increased mindfulness and self-compassion play an important role in enhancing emotional intelligence.